اعتماد الاخصائيين النفسانيين على اليوتيوب في علاج مرض التوحد لدى الاطفال - اكرام بن سعيد; خنشة أنفال; أ - د - عطا الله طريف (جامعة عمار ثليجي الاغواط, 2023)
ملخص الدراسة : هدفت هذه الدراسة معرفة استخدامات والاعتماد الأخصائي النفسي على اليوتيوب في تحقيق النتائج الايجابية لدى مرض التوحد ، لذلك كانت التساؤل الرئيسي كما يلي : -ما مدى اعتماد الأخصائيين النفسانيين على اليوتيوب في علاج مرض التوحد . وتمع اعتماد على المنهج الوصفي بهدف وصف الظاهرة وجمع أكبر عدد ممكن من المعلومات حول موضوع دراسة ، وتوصلت الدراسة الى النتائج التالية : -مرض التوحد هو اضطراب نمائي شامل يشمل عدة مراحل من حياة الطفل المصاب بالتوحد و يؤثر على عدة جوانب منها: الجانب الاجتماعي و النفسي, يولد به الطفل اسبابه مجهولة لحد الان يوجد له فرضيات فقط , الفئة الاكثر تعرضا هم الذكور . -اعراضه : نقص التواصل البصري , نقص التواصل الاجتماعي , نقص الحنان و عناق الام , نقص اللغة , رفرفة اليدين , النمطية مثل تدوير الاشياء و دوران حول النفس , الفعل العدواني سواء اتجاه النفس او الغير . -يعتمدون الاخصائين الانفسانين على اليوتيوب Youtube بشكل كبير من خلال مشاهدتهم على احدث الطرق و البرامج و الافكار, و متابعتهم لمجموعة من الاخصائين مثل "ريم الغيطي" ,"صحبة امل" "ليلى ربحاوي". -يتيح اليوتيوب Youtube التعرف على احدث طرق التشخيص و العلاج من خلال اخذ مهارات معرفية و نشاطات ترفيهية موسيقى و تربية حركية كما انه ناجح الى حد كبير من خلال مساعدتهم على تغيير و تجديد طرق العلاج. Study summary: This study aimed to know the uses and reliance of the psychologist on YouTube in achieving positive results for autism, so the main question was as follows: To what extent do psychologists rely on YouTube in treating autism? And with the reliance on the descriptive approach in order to describe the phenomenon and collect the largest possible number of information on the subject of the study, and the study reached the following results: Autism is a comprehensive developmental disorder that includes several stages of the life of an autistic child and affects several aspects, including: the social and psychological aspect, the child is born with it, its causes are unknown until now, there are only hypotheses for it, the most vulnerable group are males. Symptoms: lack of visual contact, lack of social communication, lack of tenderness and mother's hug, lack of language, hand flapping, stereotyping such as rotating things and spinning around oneself, aggressive action, whether towards oneself or others. - Psychologists rely heavily on Youtube by watching them on the latest methods, programs and ideas, and following a group of specialists such as "Reem Al-Ghaiti", "Sohabat Amal" and "Laila Rabhawi". Youtube allows people to learn about the latest methods of diagnosis and treatment by taking cognitive skills, recreational activities, music and motor education, and it is largely successful by helping them change and renew treatment methods.
دراسة ميدانية بالمركز البيداغوجي للمعاقين ذهنيا رقم 2 بالأغواط